Identification of Eggs and Spawning Zones of Hairtail Fishes Trichiurus (Pisces: Trichiuridae) in Northern South China Sea, Using DNA Barcoding - Hou, Gang; Xu, Youwei; Chen, Zuozhi; Zhang, Kui; Huang, Wangsu; Wang, Jinrun; Zhou, Jinlong (Frontiers in Environmental Science, 2021)
Commercially important hairtails, Trichiurus spp., are widely distributed throughout China’s marine waters. Because eggs of these species are difficult to identify and the taxonomy of the group has recently been resolved, their spawning grounds in the northern South China Sea (SCS) are not well known. We identified three Trichiurus species (T. japonicus, T. nanhaiensis, and T. brevis) using DNA barcodes in spring and late summer–autumn ichthyoplankton surveys of 2019 in the northern SCS. Egg distributions reveal that the spawning grounds of T.japonicus and T.nanhaiensis occur mainly from the central and southern Beibu Gulf, along Hainan Island, to the waters off the Pearl River Estuary, and that egg densities are higher in spring than in late summer-autumn. Spawning of T. japonicus commonly occurs along the continental shelf, T. nanhaiensis along the continental shelf to slope (over seabed depths of 42–380 m), and T. brevis mainly in shallow water. Considering the salinity and temperature data, we found that the eggs of Trichiurus were associated with specific water masses. In spring, eggs of T. japonicus and T. nanhaiensis occurred at central and southern Beibu Gulf water mass (CSBGWM) and South China Sea surface water mass (SCSWM). While in late summer-autumn, eggs of T. japonicus and T. nanhaiensis mainly occurred in the waters of SCSWM. Our findings reveal that the occurrence of Trichiurus eggs and their spatial and temporal distribution are determined by hydrological conditions.